2018
DOI: 10.1177/1066896918767547
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Stromal Sarcoma With Hyalinizing Giant Rosettes, Mimicking Low-Grade Fibromyxoid Sarcoma

Abstract: We highlight a rare variant pattern of low-grade endometrial stromal sarcoma showing extensive collagenous rosette formation, closely mimicking low-grade fibromyxoid sarcoma. Additionally, this neoplasm showed diffuse and strong expression of muscle markers, favoring an initial diagnosis of leiomyosarcoma. Reverse transcription-polymerase chain reaction showed the presence of JAZF1-SUZ12 fusion transcripts, and this highlights the broad morphologic and immunophenotypic spectrum of endometrial stromal sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…CD117, however, is negative in LGFMS 3,11. Rare cases of primary vulvovaginal low-grade endometrial stromal sarcoma (LGESS) have been reported,32,33 and LGESS with fibromyxoid features may resemble LGFMS,34 including rare cases of LGESS with collagen rosettes 35. High-grade endometrial stromal sarcoma with BCOR alterations may assume a multilobulated fibromyxoid appearance,36 but these are primary to the uterus and show brisk mitoses and necrosis; vulvovaginal forms of BCOR -altered high-grade endometrial stromal sarcoma have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…CD117, however, is negative in LGFMS 3,11. Rare cases of primary vulvovaginal low-grade endometrial stromal sarcoma (LGESS) have been reported,32,33 and LGESS with fibromyxoid features may resemble LGFMS,34 including rare cases of LGESS with collagen rosettes 35. High-grade endometrial stromal sarcoma with BCOR alterations may assume a multilobulated fibromyxoid appearance,36 but these are primary to the uterus and show brisk mitoses and necrosis; vulvovaginal forms of BCOR -altered high-grade endometrial stromal sarcoma have not been described.…”
Section: Discussionmentioning
confidence: 99%